Bioactivity of Crude Extract of Cashew Nut Shell (Anacardium occidentale L.) against Cabbage Head Caterpillar (Crocidolomia pavonana F.) - Mia Sukma Dewi; Danar Dono; Sri Hartati (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
The crude extract of Anacardium occidentale was reported to have insektisidal activity against Cricula trifenestrata (Lepidoptera). Althought, the extract has not been tested against Crocidolomia pavonana (Lepidoptera). A research was carried out to test the effect of cashew nut shell extract on larvae and fecundity of adult female of C. pavonana. Toxicity of the extract tested by using feeding method to the larvae. The experiment arranged in the complete randomized design (CRD), consisted of 7 treatments and 3 repetitions. The treatments were the concentration of the extract i.e. 0.8%, 0.6%, 0.4%, 0.2%, 0.1%, and 0.05%. The same treatment methode was used to test the fecundity of C. pavonana female that developed from larval treated extract at concentrations of 0.16 % (LC30), 0.30 % (LC50), 0.45 % (LC70), and control. The results of the experiment showed that the extract of A. occidentale was toxic to larvae of C. pavonana with LC50 values of 0.30 % at six days after application. The extract of A. occidentale have an antifeedant effect and lengthened the development time of the larvae. The concentration range 0.16 % - 0.45 % reduced the weight of pupa, lengthened emergence time of adult, slowed down the first oviposition, reduced the egg production, shortened the life span of adult female and male, shortened the periode of oviposition of adult female, and decreased the fertility. Keywords: Crude extract of Anacardium occidentale, Crocidolomia pavonana, toxicity, fecundity